The “filler effect”: A study of solid oxide fillers with β-Li3PS4 for lithium conducting electrolytes - Hood, Zachary D.; Wang, Hui; Li, Yunchao; Pandian, Amaresh Samuthira; Parans Paranthaman, M.; Liang, Chengdu (Solid state ionics, 2015)
Solid electrolytes are the subject of intense study partly because of their use in safer, high energy density, all-solid-state lithium-ion batteries. The addition of solid oxide fillers has been previously explored as a way to increase the ionic conductivity in composite electrolytes; however, no comparative study of the effect of both ion-conducting and non-conducting oxides on solid lithium superionic conductor electrolyte is reported. Nano-crystalline β-Li3PS4 (LPS) was recently shown to have anomalous high ionic conductivity, but it was found that this property can be further enhanced. This study examines the effect of three solid oxide fillers (Li6ZnNb4O14, Al2O3, and SiO2) in composites with LPS for the enhancement of the parent electrolyte. The electrolytes' processability, ionic conductivity, activation energy, and stability against metallic lithium are presented to gain a complete understanding on the effect of solid oxide fillers on LPS while elucidating the significant enhancement of LPS through the addition of Li6ZnNb4O14 or Al2O3. •Easy fabrication containing β-Li3PS4 (LPS) with solid oxide fillers is reported.•Ion-conducting and non-conducting fillers enhance ionic conductivity of LPS.•Solid oxide fillers decrease the Arrhenius activation energy of LPS.•Composites show prolonged stability against metallic lithium anode.•Excellent cycling performance was achieved with composite electrolytes.